2015
DOI: 10.4103/0259-1162.153763
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of intrathecal clonidine and dexmedetomidine on characteristics of bupivacaine spinal block for lower limb surgeries

Abstract: Introduction:Intrathecal clonidine or dexmedetomidine has improved the quality of spinal anesthesia, this clinical study was undertaken to assess the behavior of intrathecal clonidine as an adjuvant to bupivacaine in augmenting sensory block in patients undergoing lower limb surgeries.Materials and Methods:We studied 150 patients, between 18 and 60 years of age, patients were randomly divided into three groups of 50 each Group B: 0.5% bupivacaine 15 mg + 0.5 ml normal saline Group C: 0.5% bupivacaine 15 mg + 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
4
15
0
1
Order By: Relevance
“…An ideal local anesthetic agent used in spinal anesthesia should have rapid onset of action, intense analgesia, and adequate motor blockade, long duration of action, adequate postoperative analgesia and minimal cardiovascular changes. 1 Most anesthesiologist concern that reduced dose of local anesthetic may provide insufficient spinal block. Thus there have been many trials to reduce the dose of intrathecal local anesthetics and improve their block quality with co administration of additives such as clonidine and opioids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An ideal local anesthetic agent used in spinal anesthesia should have rapid onset of action, intense analgesia, and adequate motor blockade, long duration of action, adequate postoperative analgesia and minimal cardiovascular changes. 1 Most anesthesiologist concern that reduced dose of local anesthetic may provide insufficient spinal block. Thus there have been many trials to reduce the dose of intrathecal local anesthetics and improve their block quality with co administration of additives such as clonidine and opioids.…”
Section: Discussionmentioning
confidence: 99%
“…7 The binding affinity of dexmedetomidine compared with clonidine is nearly 1:10 Thus it is hypothesized that 3 to 5 µg of intrathecal dexmedetomidine might be equipotent to 30 to 45 µg of intrathecal clonidine. Several studies have been done using different dosage of clonidine and dexmedetomidine to determine the most effective intrathecal administration with minimal side effects 1 . In our study, the intrathecal dose of dexmedetomindine selected was based on previous human studies where no neurotoxic effects have been observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Among alpha adrenergic agonists dexmedetomidine compared to clonidine is a safe and effective alternative when used as an adjuvant to bupivacaine. 4 Studies done using different doses of dexmedetomidine have proven that 5 µg and 10 µg are safe doses when used in sub arachnoid block. These doses were associated with minimal hemodynamic alterations.…”
Section: Introductionmentioning
confidence: 99%